Cpk2, a Catalytic Subunit of Cyclic AMP-PKA, Regulates Growth and Pathogenesis in Rice Blast - Selvaraj, Poonguzhali; Shen, Qing; Yang, Fan; Naqvi, Naweed I. (Frontiers in Microbiology, 2017)
The cAMP-Protein Kinase A signalling, anchored on CpkA, is necessary for appressorium development and host penetration, but indispensable for infectious growth in Magnaporthe oryzae. In this study, we identified and characterized the gene encoding the second catalytic subunit, CPK2, whose expression was found to be lower compared to CPKA at various stages of pathogenic growth in M. oryzae. Deletion of CPK2 caused no alterations in vegetative growth, conidiation, appressorium formation, or pathogenicity. Surprisingly, the cpkA∆cpk2∆ double deletion strain displayed significant reduction in growth rate and conidiation compared to the single deletion mutants. Interestingly, loss of CPKA and CPK2 resulted in morphogenetic defects in germ tubes (with curled/wavy and serpentine growth pattern) on hydrophobic surfaces, and a complete failure to produce appressoria therein, thus suggesting an important role for CPK2-mediated cAMP-PKA in surface sensing and response pathway. CPKA promoter-driven expression of CPK2 partially suppressed the defects in host penetration and pathogenicity in the cpkA∆. Such ectopic CPK2 expressing strain successfully penetrated the rice leaves, but was unable to produce proper secondary invasive hyphae, thus underscoring the importance of CpkA in growth and differentiation in planta. The Cpk2-GFP localized to the nuclei and cytoplasmic vesicles in conidia and germ tubes. The Cpk2-GFP colocalized with CpkA-mCherry on vesicles in the cytosol, but such overlap was not evident in the nuclei. Our studies indicate that CpkA and Cpk2 share overlapping functions, but also play distinct roles during pathogenesis-associated signalling and morphogenesis in the rice blast fungus.